PHYSICIAN, SCIENTIST, EDUCATOR, HEALTHCARE ORGANIZER – NATALIA SERGEEVNA KISLYAK - N.N. Volodin; D.Yu. Ovsyannikov (Pediatria. Journal named after G.N. Speransky, 2026)
N.N. Volodin, D.Yu. Ovsyannikov. Physician, Scientist, Educator, Healthcare Organizer – Natalia Sergeevna Kislyak. Pediatria n.a. G.N. Speransky. 2026; 105 (4): 44–46. DOI: 10.24110/0031-403X-2026-105-4-44-46.